2007
DOI: 10.1111/j.1574-6968.2007.00662.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and biochemical characterization of an extracellular β-glucosidase from the wood-decaying fungusDaldinia eschscholzii(Ehrenb.:Fr.) Rehm

Abstract: An extracellular beta-glucosidase was purified from culture filtrates of the wood-decaying fungus Daldinia eschscholzii (Ehrenb.:Fr.) Rehm grown on 1.0% (w/v) carboxymethyl-cellulose using ammonium sulfate precipitation, ion-exchange, hydrophobic interaction and gel filtration chromatography. The enzyme is monomeric with a molecular weight of 64.2 kDa as estimated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and has a pI of 8.55. The enzyme catalyzes the hydrolysis of p-nitrophenyl-beta-D-gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…The result of this study agrees with some earlier reports in which many commercial β -glucosidases have been reported to exhibit optimum activity at acidic pH regions. Singhania and Karnchanatat et al reported similar optimum pH of 5.0 for β -glucosidase from A. niger NII 08121 and Daldinia eschscholzii , respectively [36, 37]. β -glucosidases from various species of Penicillium have been reported to have optimum pH range of 4.0–6.0 [3840].…”
Section: Resultsmentioning
confidence: 99%
“…The result of this study agrees with some earlier reports in which many commercial β -glucosidases have been reported to exhibit optimum activity at acidic pH regions. Singhania and Karnchanatat et al reported similar optimum pH of 5.0 for β -glucosidase from A. niger NII 08121 and Daldinia eschscholzii , respectively [36, 37]. β -glucosidases from various species of Penicillium have been reported to have optimum pH range of 4.0–6.0 [3840].…”
Section: Resultsmentioning
confidence: 99%
“…The strong inhibitory effect of Mn 2+ on endoglucanase activity is consistent with previous reports of Bacillus amyloliquefaciens DL-3 and Bacillus flexus (Lee et al, 2008; Trivedi et al, 2011). An inhibitory effect on enzyme activity by metal ions usually suggests the presence of a sulfhydryl group in the active site, where oxidation by the metal ions destabilizes the conformational folding of the enzymes (Karnchanatat et al, 2007). …”
Section: Resultsmentioning
confidence: 99%
“…BGL4 Sc was shown to be highly tolerant to glucose inhibition, with a K i value of ∼70 mM. Effective inhibition by glucose is frequently observed on β-glucosidases, whose K i values range from 0.35 to 100 mM when assayed with pNPG as substrate [35]. Recently, it has been reported the identification of glucose-tolerant β-glucosidades from compositing soil fungi, which were active in the presence of 300 mM glucose [12].…”
Section: Discussionmentioning
confidence: 98%